PERLINDUNGAN HUKUM BAGI PEMBELI DALAM PERJANJIAN JUAL BELI PROPERTI SATUAN RUMAH SUSUN DENGAN POLA PRE- PROJECT SELLING GUNA MENCAPAI KEPASTIAN HUKUM - Ruth Deta Louisa; _ Suraji (Jurnal Privat Law, 2022)
This article aims to describe legal protection for consumers from buyers in terms of breach of contract carried out by apartment developer with marketing through a pre-project selling system of flats that harms the consumers. This article is types of normative legal research that used primary and secondary legal materials in the form of literature study. And to analysis all legal material writer used the syllogism method with deductive mindset. The results of this study explain that consumers which in this matter called as buyers are often placed in a disadvantaged situation in purchasing transaction with a pre-project selling system, where consumers are faced with several standard and binding clauses contained in Binding of a Sale and Purchase Agreement (PPJB), which intentionally put consumers at a weak and vulnerable position. Preventive legal protection has been given to the buyers in the transaction of units reflected in Article 42 joncto 43 Apartment Law Number 20 of 2011, repressive legal protection reflects to the existence of legal remedies reflected in Apartment Law Number 20 of 2011. Furthermore, enforcement of legal remedies are needed for apartment buyers with pre-project selling system that is disadvantaging consumers, that the developer’s actions fulfil the offense as stipulated in the Act Number 8 of 1999 concerning Consumer Protection as a repressive legal protection measure.